(untitled) - Krishnamurthy, R. (Darya Ganj, New Delhi, 2003)
Contents of material: 1/ Management planning. 2/ The dynamics of organisation. 3/ General office functions. 4/ Library administration functions. 5/ Preparing for library leadership. 6/ Administrative data processing. 7/ Financial management. 8/ Library records. 9/ Managing library public relations. 10/ Public library training. 11/ Evaluating library public relations. 12/ Library planning, resources and staff training. 13/ Information technology and administration.
Keywords: Library science,Library administration